Jurnal Ilmiah Kesehatan, Vol XIII No.1 Mei 2018.ISSN 2086 - 9266 FAKTOR - FAKTOR YANG MEMPENGARUHI PERILAKU PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA IBU HAMIL DI POLI KIA UPTD PUSKESMAS CITANGKIL KOTA CILEGON - Nila Marwiyah; Doni Dahlia (Universitas Yatsi Madani, 2018)
Maintenance of oral health is important during pregnancy. The purpose of this study determine the factor affecting behavior maintenance of oral health on pregnant women at Poli KIA UPTD Puskesmas Citangk il Cilegon City in 2018. Design research is correlation the method is cross sectional. The sampels are 80 respondents by using simple random sampling. Based on the result (51,2%) dosen’t work, (62,5%) low education, (62,5%) had a sufficieent knowledge, (58 ,8%) a positive attitude, (60,0%) self efficacy is lacting, and almost the most respondents (58,8%) had a less behavior. Based on chi - square test results there is correlation between (age, work, education, knowledge, attitude, self efficacy) with behavior (p=0,001). The researcher recomended that pregnant women should fix awareness of importance to do maintenance of oral helath.